1967
DOI: 10.1136/bmj.2.5549.418
|View full text |Cite
|
Sign up to set email alerts
|

Treatment by prostatic injection of acute urinary retention due to prostatic hyperplasia.

Abstract: Diabetes and Cataract-Mc(uinness MEDBALJOURNAT seemed to show a greater response to glucose challenge than the other female groups. The numbers in the present group are too small for the significance of this observation to be assessed, and further study is required. It is possible that the diabetic with lens opacities may progress to a stage requiring cataract extraction more rapidly than a non-diabetic. This might explain the discrepancy between the lack of correlation in this survey and the reports of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

1978
1978
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
1
18
1
Order By: Relevance
“…Since then, it has been used by other authors, but always in the prostate. 10,[13][14][15] No other similar studies to ours were found in the literature and neither were references to biochemical dosages in animals noted so as to enable comparison to our findings. We studied the action of this solution in liver of guinea pig and observed that solution produced necrosis limited to the injected area and that hepatic tissue recovery occurred after four weeks with the formation of a small necrosis area 16 .…”
Section: Discussioncontrasting
confidence: 37%
“…Since then, it has been used by other authors, but always in the prostate. 10,[13][14][15] No other similar studies to ours were found in the literature and neither were references to biochemical dosages in animals noted so as to enable comparison to our findings. We studied the action of this solution in liver of guinea pig and observed that solution produced necrosis limited to the injected area and that hepatic tissue recovery occurred after four weeks with the formation of a small necrosis area 16 .…”
Section: Discussioncontrasting
confidence: 37%
“…As publications confirming the efficacy of this procedure continued, however, a growing experience in the literature developed regarding patients complaining of postinjection perineal pain, consistent with and documented as extraprostatic extravasation [2,3,5]. Therefore, transperineal injection largely lost favor as a route for injection until transrectal ultrasound (TRUS) was used for guidance, allowing for visualization of injection, reducing the possibility of inadvertent injectable backflow.…”
Section: Procedural Evolutionmentioning
confidence: 94%
“…The seminal study by Talwar and Pande triggered substantial investigation of transperineal intraprostatic injection [2,5]. As publications confirming the efficacy of this procedure continued, however, a growing experience in the literature developed regarding patients complaining of postinjection perineal pain, consistent with and documented as extraprostatic extravasation [2,3,5].…”
Section: Procedural Evolutionmentioning
confidence: 94%
“…Solution E, containing such components, was empirically used, as previously mentioned, for protatic patients in the early 21 st century in India by Roberts 6 . Since then, it has been used by other authors, but always in the prostate 6,12 . No other similar studies to ours were found in the literature and neither were references to biochemical dosages in animals noted so as to enable comparison to our fi ndings.…”
Section: Discussionmentioning
confidence: 99%